List otwarty w sprawie artykułu prof. Anny Chęćki - Skowron, Zbigniew (Przestrzenie Teorii, 2025)
A letter to Prof. Anna Chęćka contains its author’s commentary on her impartiality-free and deprecating evaluation of Prof. Zbigniew Skowron’s translation of Roger Scruton’s Aesthetics of Music, published by the Polish Music Publishing House in 2024. The ethical nature of this assessment is called into question by the fact that Prof. Anna Chęćka was herself the scientific editor of this translation.